2021
DOI: 10.1002/hrm.22083
|View full text |Cite
|
Sign up to set email alerts
|

How and when do prior international experiences lead to global work? A career motivation perspective

Abstract: While research suggests a link between individuals' prior international experiences and their future participation in global work, we know little about how and the conditions under which this relationship occurs. Drawing on career motivation theory, we conceptualize global identity as a mediator between individuals' density of prior international experiences-defined as the extent to which time spent in culturally novel countries has provided individuals with developmental opportunities-and their global work as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…Similarly, the need for future research on re-expatriation situations has been emphasized (e.g. Akkan et al ., 2022). It has been discussed in the discourse that such decisions may be impacted both by pull factors (e.g.…”
Section: Current Contextual Changes and Their Implications For Sies' ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the need for future research on re-expatriation situations has been emphasized (e.g. Akkan et al ., 2022). It has been discussed in the discourse that such decisions may be impacted both by pull factors (e.g.…”
Section: Current Contextual Changes and Their Implications For Sies' ...mentioning
confidence: 99%
“…As global work experiences are demanding and transitional experiences for individuals (Kraimer et al ., 2022), there has been interest in understanding what kind of impacts they make on individuals' identity. It has been reported that global careerists develop a global career identity (Akkan et al ., 2022; Suutari and Mäkelä, 2007), e.g. they also are often highly committed to working in global career environments in the future, view their job markets as global and constantly are looking for new challenges and development opportunities.…”
Section: Current Contextual Changes and Their Implications For Sies' ...mentioning
confidence: 99%
See 2 more Smart Citations